THE PUBLIC SPACE OF THE CITY AS A TOOL FOR STUDYING THE EMPIRICAL MANIFESTATION OF TRANSFORMATIONAL CHANGES IN SOCIETY - Lukin, S. (Pressing Problems of Public Administration, 2019)
The article presents the interpretation of the concept of public space of the city in order to attempt to represent it as an empirical manifestation of transformational changes in society. Accordingly, the term “space”, an overview of the evolution of the concept of “public space of the city”, functional aspects of design of public space of the city and main tendencies of its development at the present stage are outlined. The important direction of foreign studies of public spaces is considered, namely spatial analysis and planning aspects, which are being planned by the new formula at the present stage of transformational changes of society. The area of public space and the limits of its publicity are extremely different in different cities, societies, transforming themselves under the influence of economic, social, political, geographical, historical and cultural factors. An important area of foreign studies of public spaces is their spatial analysis and planning aspects. New public spaces are planned using the following formula: “first buildings, then spaces, then (perhaps) life”. The result of applying this rule when planning the spatial development of a city is the uneven distribution of public spaces throughout the city with significant differentiation of the center-neighborhood. Therefore, in this article we present modern characteristics of the city’s public space, namely spatial analysis and planning aspects that can be traced to changes occurring in urban areas, we consider as one of the steps towards building a methodological toolkit for exploring changes in the modern city. Continuing the development of ideas presented in the article, the author sees the unveiling of the heuristic potential of exploring the public space of the city to identify the social contradictions reflected in public space; as well as the development of specific tools for reflecting the transformational changes of society.